Ocean mixing induced by three-dimensional structure of equatorial mode tropical instability waves in the Pacific Ocean - Fang, Liyuan; Ma, Kai; Liu, Chuanyu; Wang, Xiaowei; Wang, Fan (Frontiers in Marine Science, 2023)
Observations have revealed that tropical instability waves (TIWs) play an important role in the ocean mixing of the equatorial thermocline. However, most studies have not distinguished the individual effects from the TIWs’ two modes, and most of them focused on the effect of the TIW-induced vertical shear on the formation of mixing. In this study, we utilize the high-resolution ocean reanalysis data to isolate the 3D structure of the equatorial mode of TIW (eTIW) and examine the detailed mechanisms of its mixing effects. Horizontally, the temperature associated with the eTIWs shows a centrosymmetric structure in the upper layers, but vertically, the phase begins to transition at 70 and becomes opposite to that of the upper layer below 90 m. The centrosymmetric temperature structure leads to a similar stratification pattern in the upper layers. We find that the pattern of the eTIW-associated reduced shear squared (RSS), an indicator for potential shear instability, is controlled by its stratification rather than shear, suggesting that the former plays a more important role than the latter in resulting in shear instability and mixing. Specifically, it is in the northern (southern) part of the clockwise (anticlockwise) phase of the eTIWs that the eTIW-associated RSS is positively large, where the total flow is more likely to be modulated by shear instability and mixing. Hence, the present study provides a new mechanism for the TIW-induced mixing in the equatorial thermocline. However, in specific regions where the eTIW-induced shear has the same sign as that of the mean flow, the eTIW-associated shear squared can also significantly enhance the total RSS and lead to shear instability, consistent with previous studies.